Acculturation and dental health among Vietnamese living in Melbourne, Australia - MarinËœo R, Stuart GW, Wright FAC, Minas IH, Klimidis S (Blackwell Synergy, 2001)
To describe the relationship between acculturation and oral health status, oral health knowledge and frequency of dental visits in subjects of Vietnamese background, 18 years or older, living in Melbourne, Australia.